Estudo do comportamento do retorno das ações ao redor da data ex-distribuição de capital no mercado acionário brasileiro - Henriques, Felipe Abad (2011)
This study aims to evaluate the behavior of the stock return around exdistribution of capital days in the Brazilian stock market. Using the event study methodology we found evidences of an abnormal return around the event. It was found that the abnormal return persists among the period from 2000 to 2010. Additionally, we verify that for the Brazilian market it is not possible to assign the effect of taxes the cause of the abnormal results.